Adsorption of binary CO2/CH4 mixtures using carbon nanotubes: Effects of confinement and surface functionalization. Issue 7 (2nd May 2016) - Wang, Shanshan; Lu, Linghong; Lu, Xiaohua; Cao, Wei; Zhu, Yudan
ABSTRACT: Effect of confinement and surface functionalization in carbon nanotubes (CNTs) on the competitive adsorption of a binary CO2 /CH4 mixture has been investigated by grand canonical Monte Carlo simulations. Adsorption using CNTs with different functionalization arrangements, different diameters, different functionalization degrees, and different functional groups, such as –COOH, –CO, –OH, –CH3, is investigated. Effects of (a) the pore textural properties, such as pore size and accessible surface area, and (b) the gas–adsorbent interaction, especially the electrostatic interaction, are discussed. From these results, we discuss the impact that variables such as confinement and surface functionalization have on the performance for CO2 separation.